2015
DOI: 10.5338/kjea.2015.34.3.29
|View full text |Cite
|
Sign up to set email alerts
|

Residual Patterns of Insecticides Bifenthrin and Chlorfenapyr in Perilla Leaf as a Minor Crop

Abstract: BACKGROUND: It is important to understand residual patterns of pesticides applied on crops for ensuring their safety in agricultural products. However, there are few studies on the residual patterns of pesticides in minor crops, which are small in cultivation area. In this study, residual amounts of bifenthrin and chlorfenapyr sprayed on perilla leaf as a minor crop were investigated to know their residual patterns. METHODS AND RESULTS: Bifenthrin and chlorfenapyr were sprayed 2 or 3 times on perilla leaves at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…Several studies have reported that the dilution effect caused by crop growth is a major factor that contributes to the decline of pesticides 19 . In another study, Jeon et al 21 discovered that the decreasing residual level of bifenthrin in perilla leaves over time was due to the growth of the plant. Furthermore, Kim et al 22 reported that the half-lives of chlorpyrifos and procymidone in lettuce were 1.2 to 1.5 days and 1.3 to 2.6 days, respectively and the major cause of the decrease over time was the growth dilution factor.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that the dilution effect caused by crop growth is a major factor that contributes to the decline of pesticides 19 . In another study, Jeon et al 21 discovered that the decreasing residual level of bifenthrin in perilla leaves over time was due to the growth of the plant. Furthermore, Kim et al 22 reported that the half-lives of chlorpyrifos and procymidone in lettuce were 1.2 to 1.5 days and 1.3 to 2.6 days, respectively and the major cause of the decrease over time was the growth dilution factor.…”
Section: Resultsmentioning
confidence: 99%
“…연작으로 재배되는 특성에 따라 재배할 때 해충, 잡초, 병에 의한 손실을 줄이고 생산량과 품 질을 증가시키기 위해 다양한 농약을 사용하고 있다 [8]. 그러 나 쑥갓을 포함한 소면적 재배작물은 재배면적과 농약 사용 량이 적어 쌀과 같은 주요 재배작물에 비해 등록되어 활용 가 능한 농약 수가 제한적이다 [9]. 현재 우리나라는 PLS 제도를 시행하고 있어, 해당 작물에 등록되지 않은 농약이 검출되면 0.01 mg/kg의 잔류량 기준이 적용, 이를 초과하여 부적합으 로 판정된 농산물은 전량 폐기되어 농민에게 경제적인 영향 을 줄 수 있다 [10].…”
unclassified